2012
DOI: 10.1038/aps.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

High-sodium intake aggravates myocardial injuries induced by aldosterone via oxidative stress in Sprague-Dawley rats

Abstract: Aim: To evaluate the effects of aldosterone with or without high sodium intake on blood pressure, myocardial structure and left ventricular function in rats, and to investigate the mechanisms underlying the effects. Methods: Eight-week-old male Sprague-Dawley rats were randomly divided into 3 groups: (1) control (CON) group fed a normal sodium diet, (2) aldosterone (ALD) group receiving aldosterone infusion and a normal sodium diet, and (3) high sodium plus aldosterone (HS-ALD) group receiving 1% NaCl diet in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…IL-1β and IL-18 are two inflammatory cytokines implicated in various kinds of CKD, and several studies demonstrated that IL-1β and IL-18 could induce expression of mesenchymal markers in tubular epithelial cells [ 25 , 26 ]. It has also been demonstrated that IL-1β and IL-18 are significantly increased in Aldo-induced renal inflammation and fibrosis in vivo [ 27 , 28 ], suggesting that IL-1β and IL-18 may be the key mediators of Aldo-induced renal injury, although the exact mechanisms remained unclear. In present study, we demonstrate that Aldo stimulation induces the production of mature IL-1β/IL-18 in renal tubular cells in a dose- and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β and IL-18 are two inflammatory cytokines implicated in various kinds of CKD, and several studies demonstrated that IL-1β and IL-18 could induce expression of mesenchymal markers in tubular epithelial cells [ 25 , 26 ]. It has also been demonstrated that IL-1β and IL-18 are significantly increased in Aldo-induced renal inflammation and fibrosis in vivo [ 27 , 28 ], suggesting that IL-1β and IL-18 may be the key mediators of Aldo-induced renal injury, although the exact mechanisms remained unclear. In present study, we demonstrate that Aldo stimulation induces the production of mature IL-1β/IL-18 in renal tubular cells in a dose- and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Activated NLRP3 inflammasome then promotes tissue injury by upregulating pro-inflammatory cytokines IL-18 and IL-1β [ 6 ]. Previous studies have reported markedly elevated IL-18 and IL-1β levels in Aldo-induced renal inflammation and fibrosis in vivo [ 7 , 8 ]. Our previous work also suggests that reactive oxygen species (ROS) participate in Aldo-induced renal injury [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous studies (4,23), our study showed that compared to matched EH controls, PA patients exhibited more renal damage indicated by reduced eGFR and greater prevalence of microalbuminuria, as well as more cardiac damage indicated by an increased prevalence of LVH. On the one hand, there is accumulating evidence including our previous researches, which support that many detrimental effects of aldosterone excess are involved in causing pre-clinical TOD in the PA patients; they include inflammation, oxidative stress, endothelial dysfunctions, and vascular calcification (7,(24)(25)(26)(27). On the other hand, a majority of patients with MetS, a cluster of risk factors, tend to develop structural and functional abnormalities of target organs, which precede cardiovascular complications (28,29).…”
Section: Discussionmentioning
confidence: 92%